A model order reduction framework for performance-based seismic design optimization of friction-tuned mass dampers in large-scale L-shaped buildings with shear cores - de Salles, Humberto B.; Fadel Miguel, Leandro F.; Lenzi, Marcos Souza; Lopez, Rafael Holdorf (Structures (Oxford), 2025)
L-shaped buildings experiencing seismic-induced oscillations are prone to stress concentrations at their re-entrant corners. Thus, the conventional rigid diaphragm assumption for slabs may not apply, requiring a more refined finite element model. A thorough literature review indicates that studies on reliability-based design optimization of tuned mass dampers are limited, and even more scarce in the context of L-shaped buildings. Nonetheless, linear behavior is assumed for the tuned mass dampers, and the lateral resistance system of the L-shaped host structure relies solely on moment-resisting frames. In this context, no existing literature addresses L-shaped buildings with nonlinear friction-tuned mass dampers, which can lead to more cost-effective maintenance programs, even in a deterministic setting, to the best of the authors’ knowledge. Thus, this paper introduces a novel performance-based seismic design optimization framework for multiple nonlinear friction-tuned mass dampers in L-shaped buildings with shear cores, modeled using shell finite elements. Given that the host structure results in a large-scale system with thousands of degrees of freedom, a non-modal model order reduction approach is employed to alleviate the substantial computational burden. The optimization goal is to minimize expected life-cycle damage costs for both serviceability and collapse limit states by determining occurrence probabilities and translating them into expected economic losses using inventory guidelines. The application case involves a 4-story L-shaped building with 8,688 active degrees of freedom. Control scenarios include single and multiple translational unidirectional friction-tuned mass dampers installed at the tips of the wings on the top floor. The results demonstrate that a significant reduction in expected damage costs can be achieved.